DIFFERENCES BETWEEN MEN AND WOMEN WITH LUNG CANCER BY SMOKING HABIT - Dimitrievska, Ljubica; Grivcevska, Milena; Grozdanovski, Toni; Alabakovska, Viktorija (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
Lung cancer is one of the most common causes of mortality in the world, coming right after cardiovascular diseases. The reason for the research is the fact that the number of newly diagnosed and death cases from lung cancer is constantly growing, especially in the last few years. The aim of the research was to further explore gender differences in lung cancer risk associated with smoking. The research is an analytical study. It includes all the patients with a confirmed diagnosis of lung cancer (LC) with histopathological analysis (investigate group) in a period of six months. Survey data was collected using a specially designed questionnaire. In the study participated 160 respondents, male and female patients. Regarding the habit of smoking cigarettes, the largest percentage of the male patients (64%) are current smokers, compared to the female patients where the largest percentage (27%) are also current smokers. According to the results obtained during the analysis, it was shown that the two groups differ significantly when it comes to the habit of smoking cigarettes. This research confirmed the association of cigarette smoking habit and lung cancer with gender differences, where several variables related to smoking were examined (age at which cigarette smoking starts, number of cigarettes smoked per day, length of smoking status, type of cigarettes). Key words: Lung cancer; gender; death; smoking habit.